Greenwashing vs Transparency: A Bibliometric Perspective - Judijanto, Loso; Siregar, Nurganda; Arini, Rani Eka (Westscience Press, 2025)
Greenwashing and transparency have emerged as two competing yet interconnected paradigms in the discourse on corporate sustainability. While greenwashing represents the manipulation or exaggeration of environmental performance, transparency reflects a firm’s commitment to honest, verifiable disclosure. This study employs a bibliometric analysis using VOSviewer to map the intellectual structure, thematic evolution, and collaborative patterns in the academic literature related to these two concepts. Based on a curated dataset from the Scopus database covering publications from 2000 to 2024, the analysis applies co-authorship, citation, co-word, and country collaboration techniques to uncover key contributors, emerging topics, and research gaps. Findings reveal that greenwashing remains a dominant theme, deeply embedded in literature on ESG, accountability, and sustainability reporting, while transparency is increasingly linked to digital technologies and financial instruments aimed at ensuring reporting credibility. Thematic clusters show evolving interest in areas such as green finance, blockchain, and supply chain transparency. Author and institutional networks reflect growing international collaboration, though notable disparities exist in geographic representation. This study contributes to a clearer understanding of the academic field and provides a foundation for future interdisciplinary research aimed at combating greenwashing and promoting transparent corporate sustainability practices.